Application of Cockle (Anadara granosa) Shell Waste as an Adsorbent of Heavy Metal Cadmium (Cd), Copper (Cu), and Lead (Pb) - Mirni Lamid; Sugijanto Sugijanto; Akbar Falah Tantri (Journal of Aquaculture and Fish Health, 2022)
Heavy metal is one of the water pollutants that are harmful to the environment and humans. Cockle (Anadara granosa) is only used for meat so that the shells become waste that pollutes the environment. This study examines the ability of cockle shell powder as an adsorbent in the process of adsorption of heavy metals cadmium (Cd), copper (Cu), and lead (Pb). The ability of the adsorbent was tested through the batch method, using a glass beaker (100 ml) at a speed of 90 rpm; initial metal concentration 20 ppm; adsorbent weighing 0.1 – 0.5 grams; contact time of 20 minutes and 30 minutes. The results showed that the adsorbent weighing 0.5 grams can reduce > 75% concentration of cadmium (Cd), copper (Cu), and lead (Pb). Freundlich and Langmuir adsorption isotherms of cadmium (Cd), copper (Cu), and lead (Pb) had R2 > 0.9.